Achilles mechanism reconstruction in four dogs Murdoch University Veterinary Hospital, Murdoch, WA, Australia - Sivacolundhu, R. K.; Marchevsky, A. M.; Read, R. A.; Eger, C. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Chronic Achilles mechanism injuries require aggressive treatment with excision of degenerate tissue. Following excision of degenerate tendon, the defect created may be too large to allow simple apposition of tendon to bone. Use of peroneus brevis and peroneus longus tendon transpositions (passing through bone tunnels drilled in the calcaneus), +/− lengthening of the gastrocnemius tendon, and reinforcement with a free fascial strip graft allows reconstruction of the area. Postoperative support should be provided using a type II transarticular external fixator for four weeks, followed by a splint or Robert Jones bandage for three weeks. Treatment, in all four of the dogs in this report, resulted in a good to excellent outcome. Based on the favourable results in this series, resection of all grossly abnormal tendon should be considered in cases of Achilles mechanism rupture, even though reconstruction of the area is more complex.Five Achilles mechanism reconstructions were performed in four dogs with chronic injury to the tendon. Following excision of degenerate tendon the area was reconstructed, in each case using peroneus brevis and peroneus longus tendon transpositions, lengthening of the gastrocnemius tendon and reinforcement with a free fascial strip graft. Post-operative support was provided in the form of a type II trans-articular external fixator for four to five weeks, followed by a splint or Robert Jones bandage for two to three weeks. The results in all of the dogs were good to excellent. One dog returned to full working capacity. Two dogs returned to unrestricted exercise without any observable lameness. One dog (bilateral injury) is sound but the owners have decided to limit the dog’s access to unrestricted activity.
Keywords: Achilles mechanism; Achilles tendon; peroneus brevis; peroneus longus; fascial strip graft; dog